What does the history of Theraphosidae systematics tell us about the future of tarantula taxonomy? - Briggs, Ethan J.; Hamilton, Chris A. (Frontiers in Arachnid Science, 2024)
Systematics provides the foundational knowledge about the units of biodiversity, i.e., species, and how we classify them. The results of this discipline extend across Biology and can have important impacts on conservation. Here we review the systematic and taxonomic practices within Theraphosidae over the last 260 years. We examine the rate of newly described species and investigate the contemporary practices being used in the description of new genera and species. There have been two large waves of theraphosid taxonomy, with an explosive growth of newly described species and author combinations in the last 60 years. We look back and find that during 2010-2024 contemporary practices in theraphosid systematics and taxonomy have remained largely static, being dominated by morphology-based approaches. Over this period, only 10% of newly described species incorporated DNA data or explicitly stated the species concept used. Similarly for genera, only five of the 37 newly described genera over that time were supported as distinct and monophyletic by DNA. We highlight the taxonomic movement of species amongst Theraphosidae, Barychelidae, and Paratropididae; however, given the limited molecular sampling for the two latter families, the boundaries of these families remain a significant area of needed research. To promote inclusivity, we provide a copy of this paper in Spanish as supplementary material.